Genetics of Duchenne and Becker Dystrophies - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1990)
The molecular basis for Duchenne and Becker muscular dystrophies is reviewed from the Department of Pediatric Neurology, Floating Hospital for Infants and Children, New England Medical Center Hospitals and Tufts University, Boston, Mass.